Re‐Os isotope and platinum group elements of a FOcal ZOne mantle source, Louisville Seamounts Chain, Pacific ocean. (19th February 2015) - Tejada, Maria Luisa G.; Hanyu, Takeshi; Ishikawa, Akira; Senda, Ryoko; Suzuki, Katsuhiko; Fitton, Godfrey; Williams, Rebecca
Abstract The Louisville Seamount Chain (LSC) is, besides the Hawaiian‐Emperor Chain, one of the longest‐lived hotspot traces. We report here the first Re‐Os isotope and platinum group element (PGE) data for Canopus, Rigil, and Burton Guyots along the chain, which were drilled during IODP Expedition 330. The LSC basalts possess (187Os/188Os)i = 0.1245–0.1314 that are remarkably homogeneous and do not vary with age. A Re‐Os isochron age of 64.9 ± 3.2 Ma was obtained for Burton seamount (the youngest of the three seamounts drilled), consistent with 40Ar‐39Ar data. Isochron‐derived initial 187Os/188Os ratio of 0.1272 ± 0.0008, together with data for olivines (0.1271–0.1275), are within the estimated primitive mantle values. This (187Os/188Os)i range is similar to those of Rarotonga (0.124–0.139) and Samoan shield (0.1276–0.1313) basalts and lower than those of Cook‐Austral (0.136–0.155) and Hawaiian shield (0.1283–0.1578) basalts, suggesting little or no recycled component in the LSC mantle source. The PGE data of LSC basalts are distinct from those of oceanic lower crust. Variation in PGE patterns can be largely explained by different low degrees of melting under sulfide‐saturated conditions of the same relatively fertile mantle source, consistent with their primitive mantle‐like Os and primordial Ne isotope signatures. The PGE patterns and the low 187Os/188Os composition of LSC basalts contrast with those of Ontong Java Plateau (OJP) tholeiites. We conclude that the Re‐Os isotope and PGE composition of LSC basalts reflect a relatively pure deep‐sourced common mantle sampled by some ocean island basalts but is not discernible in the composition of OJP tholeiites.